A comparative analysis of criminal offenses against the judicial process under Indonesian Law No. 1 of 1946 and Law No. 1 of 2023 - Al-Aqhsa, Ghazi; Jeumpa, Ida Keumala (Geuthèë Institute, Aceh, 2025)
Criminal offenses that interfere with the administration of justice remain prevalent in practice, yet they have historically been under-prosecuted, primarily due to the absence of clear and explicit legal provisions under Indonesian Law No. 1 of 1946. This Law regulates such conduct only implicitly, resulting in uncertainty in application and hinders effective enforcement. By contrast, Indonesian Law No. 1 of 2023 establishes a clearer and more comprehensive legal framework for addressing offenses against the judicial process. This study seeks to undertake a doctrinal comparative analysis of the two legislative instruments, focusing on the classification of offenses, the corresponding penal sanctions, and the legal subjects to whom the provisions apply. The study applies a normative juridical framework, combining legislative and case law analysis, and is supported by extensive library research. The research found that Law No. 1 of 2023 systematically codifies offenses against the judicial process in Chapter VI, prescribing penalties in the form of imprison. Although the statute encompasses all individuals, it expressly mandates heightened sanctions for violations committed by law enforcement authorities, an aspect not addressed in the 1946 law. The study advocates for further refinement of the 2023 statute to address unregulated acts and proposes a more specific categorization of offenses to ensure greater legal precision and facilitate effective prosecution